From Random Perturbation to Precise Targeting: A Comprehensive Review of Methods for Studying Gene Function in Monascus Species - Yunxia Gong; Shengfa Li; Deqing Zhao; Xi Yuan; Yin Zhou; Fusheng Chen; Yanchun Shao (Journal of Fungi)
Monascus, a genus of fungi known for its fermentation capability and production of bioactive compounds, such as Monascus azaphilone pigments and Monacolin K, have received considerable attention because of their potential in biotechnological applications. Understanding the genetic basis of these metabolic pathways is crucial for optimizing the fermentation and enhancing the yield and quality of these products. However, Monascus spp. are not model fungi, and knowledge of their genetics is limited, which is a great challenge in understanding physiological and biochemical phenomena at the genetic level. Since the first application of particle bombardment to explore gene function, it has become feasible to link the phenotypic variation and genomic information on Monascus strains. In recent decades, accurate gene editing assisted by genomic information has provided a solution to analyze the functions of genes involved in the metabolism and development of Monascus spp. at the molecular level. This review summarizes most of the genetic manipulation tools used in Monascus spp. and emphasizes Agrobacterium tumefaciens-mediated transformation and nuclease-guided gene editing, providing comprehensive references for scholars to select suitable genetic manipulation tools to investigate the functions of genes of interest in Monascus spp.